“Blame Miners, not the Government”: An Image Repair Perspective of the Oyo State Government’s Response to the Ibadan Explosion in Nigeria - Adeola Mobolaji (LSPR Institute of Communication & Business, 2025)
A compelling example of events that attracted public interest in crisis response and image repair is the recent deadly explosion in Ibadan, the capital of Oyo State, Nigeria, an event with significant implications for public safety, citizen well-being, and government credibility. This case is particularly relevant to governmental communication, as effective crisis communication strategies are vital for image repair during and after such events. Despite the frequency of crises involving Nigerian institutions, and the tendency for such crises to be politicized, there is a notable dearth of empirical studies applying Benoit’s Image Repair Theory to governmental responses. This study addresses that gap by examining how the Oyo State Government restored its image and reputation following the explosion. Using Image Repair Theory as a framework, the study analyzed official communications posted on the Oyo State government’s X (formerly Twitter) page. Findings indicate that the public rejected the government's initial denial, but image repair was achieved through corrective action and compensation. This paper argues that government must not be discreet with its crisis response strategies. The analysis, therefore, underscores the importance of transparency and political leaders' visible presence and empathy in enhancing the effectiveness of image repair strategies. These findings contribute to the crisis communication and governance literature, offering broader implications for crisis management and political accountability in Nigeria.